Nation-Building and Community in Israel - Willner, Dorothy (Princeton, NJ : Princeton University Press, 2015)
The author approaches the intricate process of nation-building in Israel through an examination of transformations which took place within a major development sector, rural land settlement, during Israel's first decade of statehood. Based on four years of observation in Israel, the study analyzes the ways in which this state worked out the urgent problems that confront a new nation, and demonstrates in vivid ethnographic detail how the policies thus formed made themselves felt in particular communities. The result is a clear picture of the interaction of national planning and the realities of village life in post-statehood Israel, and an original contribution to the anthropology of complex societies.Originally published in 1968.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Preface -- I. Introduction -- II. The Pre-Statehood Foundations of the New Society and its Land Settlement Sector -- III. The Moshav Ovdim as Model for the Moshav Olim -- IV. Organization of Land Settlement after the Establishment of the New State -- V. The Phase of Rationalization -- VI. A Burgeoning Bureaucracy and the New Society -- VII. Jews in the High Atlas Mountains of Morocco: A Partial Reconstruction -- VIII. Ometz: The First Year of a Successful Moshav Olim -- IX. Variability in Village Development -- X. Epilogue: Nation-Building and the New Society -- Glossary -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Agricultural colonies -- Israel -- Case studies; SOCIAL SCIENCE / Sociology / Rural